Two-dimensional code enables visibly mapping herbal medicine chemome: an application in Ganoderma lucidum - Qian Wang; Wenjing Liu; Bo Peng; Xingcheng Gong; Jingjing Shi; Ke Zhang; Bo Li; Pengfei Tu; Jun Li; Jun Jiang; Yunfang Zhao; Yuelin Song (BMC, 2023)
Abstract Background Chemical profile provides the pronounced evidence for herbal medicine (HM) authentication; however, the chemome is extremely sophisticated. Fortunately, two-dimensional (2D) code, as a quick response means, is conceptually able to store abundant information, exactly fulfilling the chemical information storage demands of HMs. Methods We here attempted to denote both MS $$^1$$ 1 and MS $$^2$$ 2 dataset of HM with a single 2D-code chart. Measurement of Ganoderma lucidum that is one of the most famous HMs with LC-MS/MS was employed to illustrate the "coding-decoding" workflow for the conversion amongst MS/MS dataset, 2D-code, and chemical profile, and to evaluate the applicability as well. After data acquisition, and m/z value of each deprotonated molecular signal was divided into integer and decimal portions, corresponding to x and y coordinates of 2D-plot, respectively. On the other side, m/z values of all its fragment ions were exactly assigned to serial x values sharing an identical y value being equal to the precursor ion. 2D-code was thereafter produced by plotting these defined dots at a 2D-chart. Regarding a given 2D-code map, the entire chart (x coordinate: 0-600; y coordinate: 0-600) was fragmented into two regions by the line of y=x. MS $$^1$$ 1 spectral signals always located below the line, whereas all fragment ions lay at the left zone. After extracting information from the edges of each square frame, m/z values of both precursor ion and fragment ions could be harvested and putatively deciphered to a compound through applying some empirical mass fragmentation rules. Results The entire code of Ganoderma lucidum fruit bodies therefore corresponded exactly to a compound set. The elution program, even the employment of direct infusion, couldn't significantly impact the code, and dramatical differences occurred between different species and amongst different parts of Ganoderma lucidum as well. Not only ganoderic acid cluster but also certain primary metabolites served as the diagnostic compounds towards species differentiation. Conclusion 2D-code might be a meaningful, practical visual way for rapid HM recognition because it is convenient to achieve the conversion amongst MS/MS dataset, 2D-barcode plot, and the chemome.